Bifurcation of the Equilibria of a Cylinder in a Steady Two-dimensional Channel Flow - Lipira, Zachary J.; Feng, Z. C. (Journal of Vibration Testing and System Dynamics, 2026)
The flow about a circular cylinder placed within a channel is studied numerically in order to examine the lift forces on the cylinder for Reynolds numbers below the onset of unsteady flow. It is observed that there is a critical Reynolds number between 60 and 80 that results in the lift force to become destabilizing for the cylinder equilibrium position at the center of the channel. Meanwhile, two new equilibrium positions of the cylinder away from the channel center come to existence. Associated with this bifurcation of the equilibria, the flow streamline and vorticity plots are presented.